Psychological and pedagogical aspects of adaptation of mining faculties graduates in the context of a modern enterprise - Бакум, Зінаїда; Хоцкіна, Світлана (Pedagogy of Higher and Secondary Education, 2014)
Bakum Z. P., Khotskina S. M. Psychological and pedagogical aspects of adaptation of mining faculties graduates in the context of a modern enterprise. Basing on the increasing status of adaptation processes for future industrial specialists the authors substantiate the importance to form psychological and pedagogical factors of adaptation of mining faculties graduates in the context of a modern enterprise.